Response to Biologics During the First Six Months of Therapy in Biologic-naïve Patients with Psoriasis Predicts Risk of Disease Flares: A Danish Nationwide Study - Nikolai Loft; Alexander Egeberg; Mads Kirchheiner Rasmussen; Lars Erik Bryld; Christoffer V. Nissen; Tomas Norman Dam; Kawa Khaled Ajgeiy; Lars Iversen; Lone Skov (Medical Journals Sweden, 2021)
Early response to treatment with biologics might be important for the stability of psoriasis and long-term outcome. The aim of this study was therefore to assess whether risk of flares and drug survival are associated with disease activity in the first 6 months of treatment of psoriasis with biologics. Biologic-naïve patients from the Danish nationwide registry, DERMBIO, were grouped based on absolute Psoriasis Area and Severity Index (PASI) during the first 6 months of treatment, as: PASI = 0, PASI > 0-≤2, PASI > 2-≤ 4, and PASI > 4. Among 1,684 patients, 746 achieved PASI= 0, 485 PASI > 0-≤2, 246 PASI > 2-≤4, and 207 PASI > 4. Longer flare-free period and drug survival were observed for patients with lower PASI in the first 6 months of treatment (adjusted hazard ratios for flares (95% confidence interval) with PASI=  0 as reference: PASI > 0-≤2 (1.35 (1.11-1.72]), PASI > 2-≤ 4 (2.32 [1.80-2.99]), and PASI > 4 (2.38 [1.80-3.15])). In conclusion, a low PASI in the first 6 months of treatment with biologics in biologic-naïve patients with psoriasis was associated with a more stable disease course, lower risk of flares, and longer drug survival.